Pengaruh Tension Benang Dan Kecepatan Penggulungan Benang Ulang (Rewinding) Terhadap Bulu (Hairiness) Benang Kapas Carded Ne 30/1 - Giyanto Giyanto (Universitas Islam Syekh Yusuf Tangerang, 2023)
One of the problems in the process of making cloth is the appearance of the thread which is not good. One of the causes of the appearance of the fabric is not good, one of which is the high value of the thread hair. Feathers are cotton fibers that do not get twisted in the yarn and this occurs due to the process of friction between the yarn and the metal. In the process of winding yarn on a winding machine, defects in the reel are often found, so the yarn needs to be rewound. Due to the rewinding of the yarn, the hair will increase due to the repeated friction of the yarn with the metal. For this reason, research on the causes of the increase in thread hair was carried out. The research was conducted on a winding machine using a randomized block design with three replications. The factors studied included yarn tension consisting of 10 gram, 12 gram, 14 gram yarn tention and rewinding speeds of 900 m/minute, 1000 meter per minute and 1100 meter per minute. To analyze the data using Analysis of variance (Anava). Because the expected thread hair value is as low as possible, the criterion used is the smaller the better. The experimental results show that using the optimal setting, namely the yarn tension of 10 grams, and the rewinding speed of 900 meters/minute, produces the best yarn hair value of 6.35.